The endangered epiphytic orchid Dendrobium okinawense has a highly specific mycorrhizal association with a single Tulasnellaceae fungus. Issue 3 (4th May 2021) - Rammitsu, Kento; Abe, Shin; Abe, Tetsuto; Kotaka, Nobuhiko; Kudaka, Masahiro; Kudaka, Natsuko; Kinoshita, Akihiko; Ogura-Tsujita, Yuki
ABSTRACT: Epiphytic orchids, which account for 68% of vascular epiphytes, contribute substantially to plant species diversity in forest canopies. Many orchid species are naturally rare and have limited geographical distributions. All orchids rely on mycorrhizal fungi for nutrient acquisition during seed germination and seedling establishment, and many species retain these associations throughout their lifecycle. Due to their reliance on mycorrhizal fungi, epiphytic orchid species with highly specific mycorrhizal associations may be geographically restricted and are often rare. Dendrobium okinawens e is a rare epiphytic orchid endemic to the Yambaru Forest in Japan and to southern Taiwan. We hypothesized that this species exhibits high mycorrhizal specificity and tested this hypothesis via identification of the species' mycorrhizal associates. We collected root samples of this orchid from four tree species and assessed mycorrhizal fungi in 25 root fragments harvested from 10 plants. Fungi were identified using molecular methods based on fungal isolates and DNA extracted from mycorrhizal roots. Detected fungi were assigned to 21 operational taxonomic units (OTUs) based on 97% sequence similarity of nuclear ribosomal DNA internal transcribed spacer region sequences. TU11, an OTU belonging to Tulasnellaceae (Basidiomycota), was the most frequently detected OTU, occurring in 20 root fragments from all 10 sampled individuals. Our results indicate that Dendrobium okinawense has a highly specific association with TU11. Further, this specificity may be high relative to the Dendrobium species assessed in other studies. These findings support the hypothesis that Dendrobium okinawense exhibits high mycorrhizal specificity.